Differential antigenic requirements by diverse MR1‐restricted T cells. Issue 2 (13th January 2022) - Seneviratna, Rebecca; Redmond, Samuel J; McWilliam, Hamish EG; Reantragoon, Rangsima; Villadangos, Jose A; McCluskey, James; Godfrey, Dale I; Gherardin, Nicholas A
Abstract: MHC‐related protein 1 (MR1) presents microbial riboflavin metabolites to mucosal‐associated invariant T (MAIT) cells for surveillance of microbial presence. MAIT cells express a semi‐invariant T‐cell receptor (TCR), which recognizes MR1–antigen complexes in a pattern‐recognition‐like manner. Recently, diverse populations of MR1‐restricted T cells have been described that exhibit broad recognition of tumor cells and appear to recognize MR1 in association with tumor‐derived self‐antigens, though the identity of these antigens remains unclear. Here, we have used TCR gene transfer and engineered MR1‐expressing antigen‐presenting cells to probe the MR1 restriction and antigen reactivity of a range of MR1‐restricted TCRs, including model tumor‐reactive TCRs. We confirm MR1 reactivity by these TCRs, show differential dependence on lysine at position 43 of MR1 (K43) and demonstrate competitive inhibition by the MR1 ligand 6‐formylpterin. TCR‐expressing reporter lines, however, failed to recapitulate the robust tumor specificity previously reported, suggesting an importance of accessory molecules for MR1‐dependent tumor reactivity. Finally, MR1‐mutant cell lines showed that distinct residues on the α1/α2 helices were required for TCR binding by different MR1‐restricted T cells and suggested central but distinct docking modes by the broad family of MR1‐restricted αβ TCRs. Collectively, these data are consistent with recognition of distinct antigens by diverse MR1‐restricted T cells. Abstract : The study provides evidence validating the self‐reactivity of tumor‐reactive MHC‐related protein 1 (MR1)‐restricted T cells. Furthermore, we show that these T‐cell receptors exhibit differential antigen recognition and utilize diverse docking modes to recognize MR1–antigen complexes.